Bardoxolone Methyl Ameliorates Compression-Induced Oxidative Stress Damage of Nucleus Pulposus Cells and Intervertebral Disc Degeneration Ex Vivo - Tian, Yueyang; Duan, Jiaqi; Cao, Yang; Zhou, Huichao; Diwan, Ashish D; Tu, Ji (Frontiers in Bioengineering and Biotechnology, 2022)
Intervertebral disc degeneration (IDD) is the main cause of low back pain, and little is known about its molecular and pathological mechanisms. According to reports, excessive compression is a high-risk factor for IDD; compressive stress can induce oxidative stress in nucleus pulposus (NP) cells during IDD progression that, in turn, promotes cell apoptosis and extracellular matrix (ECM) degradation. Currently, NP tissue engineering is considered a potential method for IDD treatment. However, after transplantation, NP cells may experience oxidative stress and induce apoptosis and ECM degradation due to compressive stress. Therefore, the development of strategies to protect NP cells under excessive compressive stress, including pretreatment of NP cells with antioxidants, has important clinical significance. Among the various antioxidants, bardoxolone methyl (BARD) is used to protect NP cells from damage caused by compressive stress. Our results showed that BARD can protect the viability of NP cells under compression. BARD inhibits compression-induced oxidative stress in NP cells by reducing compression-induced overproduction of reactive oxygen species and malondialdehyde. Thus, BARD has a protective effect on the compression-induced apoptosis of NP cells. This is also supported by changes in the expression levels of proteins related to the mitochondrial apoptosis pathway. In addition, BARD can inhibit ECM catabolism and promote ECM anabolism in NP cells. Finally, the experimental results of the mechanism show that the activation of the Nrf2 signaling pathway participates in the protection induced by BARD in compressed NP cells. Therefore, to improve the viability and biological functions of NP cells under compression, BARD should be used during transplantation.